Mercury in precipitated and surface snow at Dome C and a first estimate of mercury depositional fluxes during the Austral summer on the high Antarctic plateau. (1st October 2021) - Cairns, Warren RL.; Turetta, Clara; Maffezzoli, Niccolò; Magand, Olivier; Araujo, Beatriz Ferreira; Angot, Hélène; Segato, Delia; Cristofanelli, Paolo; Sprovieri, Francesca; Scarchilli, Claudio; Grigioni, Paolo; Ciardini, Virginia; et al.
Abstract: The role of deposition fluxes on the mercury cycle at Concordia station, on the high Antarctic plateau have been investigated over the Austral summer between December 2017 to January 2018. Wet/frozen deposition was collected daily from specially sited tables, simultaneously with the collection of surface (0–3 cm) and subsurface (3–6 cm) snow and the analysis of Hg 0 in the ambient air. Over the course of the experiment the atmospheric Hg 0 concentrations ranged from 0.58 ± 0.19 to 1.00 ± 0.33 ng m −3, surface snow Hg concentrations varied between (0–3 cm) 0.006 ± 0.003 to 0.001 ± 0.001 ng cm −3 and subsurface snow (3–6 cm) concentrations varied between 0.001 ± 0.001 to 0.003 ± 0.002 ng cm −3 . The maximum daily wet deposition flux was found to be 23 ng m −2 d −1 . Despite the low temporal resolution of our measurements combined with their potential errors, the linear regression of the Hg deposition fluxes against the snow accumulation rates allowed us to estimate the mean dry deposition rate from the intercept of the graph as −0.005 +- 0.008 ng m −2 d −1 . From this analysis, we conclude that wet deposition accounts for the vast majority of the Hg deposition fluxes at Concordia Station. The number of snow events, together with the continuous GEM measurements have allowed us to make a first estimation of the mean snow scavenging factor at Dome C. Using the slope of the regression of mercury flux on snow accumulation we obtained a snow scavenging factor that ranges from 0.21 to 0.22 ± 0.02 (ngHg /g snow )/(ngHg /m 3 air ). Our data indicate that the boundary layer height and local meteorological effects influence Hg 0 reemission from the top of (0–3 cm) the snowpack into the atmosphere and into the deeper snowpack layer (3–6 cm). These data will help constrain numerical models on the behaviour of mercury in Antarctica. Highlights: The daily collection of snow accumulation at Dome C station and from this an estimation of the depositional fluxes of mercury. Surface snow sublimation is apparently linked with the net release of mercury from the snowpack in the summer. Estimated of the net dry deposition velocity of mercury, the results show a net release of mercury from the snowpack. We have made a first estimation of the snow scavenging factor for mercury on the high Antarctic plateau.